Vitamin A mitigates lipopolysaccharide-induced oxidative stress in bovine mammary epithelial cells via enhancing expression and blocking interleukin-1 - Yongmei Guo; Huiyu Shi; Sumei Yan; Binlin Shi; Xiaoyu Guo; Yanli Zhao (Italian Journal of Animal Science)
The current study was conducted to reveal a protective mechanism of vitamin A (VA) attenuating lipopolysaccharide (LPS)-induced oxidative stress in bovine mammary epithelial cells (BMECs) by blocking interleukin-1 (IL-1) as well as silence and overexpression of glutathione peroxidase-1 (GPx1). In the first part, BMECs received treatments: control, VA, LPS, interleukin-1 receptor antagonist (IL-1ra), VA + LPS, VA + IL-1ra, LPS + IL-1ra and VA + LPS + IL-1ra. In the second part, BMECs were grouped: control, LPS, VA + LPS, VA + LPS + GPx1siRNA, VA + LPS + GPx1OE, VA, LPS + GPx1OE and VA + GPx1siRNA. The result of the first part showed that supplementation with VA or VA + IL-1ra improved cellular antioxidant capacity, but IL-1ra alone had no significant effects. Addition of VA + LPS or LPS + IL-1ra or VA + IL-1ra had a positive effect on activities of glutathione peroxidase and its gene expression; furthermore, these three groups had a positive effect on signalling pathways’ activation of nuclear factor erythroid 2-related factor (Nrf2) and inhibited LPS-induced nuclear factor kappa-B (NF-κB). The results of the second part showed that, compared to the VA + LPS group, GPx1 and Nrf2 gene expression were significantly lower, whereas other cytokines, as well as NF-κB p65 and NF-κB p50 expression, showed the opposite changes in cells transfected with GPx1siRNA and incubated with VA and LPS. However, the mRNA expression of GPx1 was significantly increased; meanwhile, the expression of cytokines was significantly lower in cells transfected with GPx1OE and incubated with LPS compared to the LPS group. Compared with VA + LPS group, cells transfected with GPx1OE and incubated with LPS had increased gene expression of GPx1 and Nrf2 and similar change in expression of cytokines and NF-κB p65 and NF-κB p50. In conclusion, VA increased the gene expression and activity of GPx1 by promoting Nrf2 signalling pathway and inhibiting NF-κB signalling pathway, and ultimately reduced the IL-1 over-release to play the role of pre-protection effect.